2020
DOI: 10.1016/j.ijrobp.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nodal Target Volume Definition in Breast Cancer Radiation Therapy According to RTOG Versus ESTRO Atlases: A Practical Review From the TransAtlantic Radiation Oncology Network (TRONE)

Abstract: Regional nodal irradiation has gained interest in recent years with the publication of several important randomized trials and the availability of more conformal techniques. Target volume delineation represents a critical step in the radiation planning process. Adequate coverage of the microscopic tumor spread to regional lymph nodes must be weighed against exposure of critical structures such as the heart and lungs. Among available guidelines for delineating the clinical target volume for the breast/chest wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Data on regional nodal failures stratified by delineation protocols is now emerging, and while our analysis was not designed to assess the quality of regional nodal irradiation, this is an important avenue for research and our group will be addressing it in the near future. 25 Our analysis shows that if a particular planning technique is preferred, some thought should be given to the delineation protocol best suited for it. At this time, in the absence of a local control analysis, it is impossible to decide whether ESTRO or RTOG delineation guidelines should be followed, and until such a report appears, radiation oncologists can choose either.…”
Section: Discussionmentioning
confidence: 99%
“…Data on regional nodal failures stratified by delineation protocols is now emerging, and while our analysis was not designed to assess the quality of regional nodal irradiation, this is an important avenue for research and our group will be addressing it in the near future. 25 Our analysis shows that if a particular planning technique is preferred, some thought should be given to the delineation protocol best suited for it. At this time, in the absence of a local control analysis, it is impossible to decide whether ESTRO or RTOG delineation guidelines should be followed, and until such a report appears, radiation oncologists can choose either.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that more generous CTVs may be recommended for patients with locally advanced disease. Loganadane et al also compared the nodal target volumes of the RTOG, ESTRO and RADCOMP atlases [36]. They provided detailed visual and written details about the differences between the atlases and concluded that treatment planning for patients with locally advanced disease should use the RADCOMP atlas.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between the two different approaches has been performed by a few groups and this has included mapping of location of recurrences. For some components of nodal target volumes, ESTRO volumes tend to be larger than RTOG volumes as a result of the ESTRO recommendation of adding a 5 mm margin lateral and medial (cropping the volume onto the lung surface) to the internal mammary vessels, and adding a volume to interpectoral nodal CTVn between the pectoralis major and minor [28][29][30][31]. Conversely, ESTRO volumes tend to be smaller at CTVn_level 1 toward the arm and back muscles and the CTVn_level 4 where the cranial border is reduced from the cricoid cartilage to 5 mm cranial to the subclavian vein.…”
Section: Estro Vs Rtog Vs Radcomp and Delineation In Locoregionally Advanced Breast Cancermentioning
confidence: 99%